Exploring online Interaction through Connectivism - Zakaria, Nursyuhada; Mohd Yunos, D Rohayu; Mat Shawal, Bazilah Raihan; Ahmad Afip, Liyana; Ghazali , Linira; Gill, Kavarljit Kaur (AJELP: Asian Journal of English Language and Pedagogy, 2024)
Educational institutions worldwide have been shifting away from traditional approaches to online learning due to its abundance of advantages. Despite the advantages, online learning presents challenges especially in managing an active interaction between educators and students. This study seeks to explore students’ perception of interactions in online learning from the connectivism point of view. A total of 162 participants from Universiti Malaysia Kelantan responded to the survey. Findings indicate that students perceive autonomy or learner-to-instructor interaction as the most important interaction in online learning. Additionally, this study also found that there is a strong relationship between all fundamental factors in connectivism for online learning. The outcome of this study will help educators to better understand the importance of students’ interaction with educators in promoting an active engagement among students. A prudent approach should be devised in order to provide a supportive and effective online learning ecosystem.